Effect of BaHfO3 introduction on the transport current at the grain boundaries in SmBa2Cu3Oy films. (3rd February 2015) - Tsuruta, Akihiro; Yoshida, Yutaka; Ichino, Yusuke; Ichinose, Ataru; Watanabe, Shunya; Horide, Tomoya; Matsumoto, Kaname; Awaji, Satoshi
Abstract: We report the effect of BaHfO3 (BHO) introduction into SmBa2 Cu3 O y (SmBCO) films on the transport properties at artificial grain boundaries (AGBs) by comparing pure SmBCO and BHO-doped SmBCO films deposited on bicrystal substrates. Improvement of the critical current density ( J c ) at the AGB of BHO-doped SmBCO films was confirmed under the magnetic fields at which J c was restricted at the AGB. By investigating the superconducting properties and from TEM observations, we found that the in-field J c value for BHO-doped SmBCO films was improved through flux pinning of the Abrikosov–Josephson vortices by BHO nanorods.